(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The quality of health services has become an important concern at the global level. OECD countries on average invest 6-8% of their total health budget in the development of emergency facilities and services. Meanwhile, in less developed countries, investment for emergencies is less than 2%. Efforts to improve the quality of emergency unit services are very important and strategic to carry out considering their very vital function, namely saving the lives of emergency patients. Data also shows that the quality of service achieved by emergency department health workers in many hospitals is still low, including South Sumatra. If this problem is ignored, there is a risk of increasing patient morbidity and mortality due to poor quality of emergency services. This research aims to analyze the services of emergency department health workers on patient satisfaction at Bayung Lencir Regional Hospital, MUBA Regency in 2024. This research was conducted in February-March 2024. The design of this research was quantitative with a cross-sectional approach. The population of this study were patients who received services at the emergency room at Bayung Lencir Regional Hospital in February-March 2024. The sample in this study was 100 people with a sampling technique, namely accidental sampling. Data collection and retrieval uses a questionnaire. Statistical tests used the chi-square test and multiple logistic regression test with a significance level (p value) of 0.05. The research results show that there is a significant relationship between reliability (p value 0.000), responsiveness (p value 0.002), insurance (p value 0.000) and empathy (p value 0.003) on patient satisfaction at Bayung Lencir Regional Hospital. In the multivariate analysis, the most dominant variable influencing patient satisfaction with the services of emergency room health workers at Bayung Lencir Regional Hospital was assurance (p value 0.000 OR 3.653). The conclusion of this research is that there is a relationship between reliability, responsiveness, assurance and empathy on patient satisfaction at Bayung Lencir Regional Hospital. It is recommended to correct existing deficiencies and optimize the services provided.